Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Investigation of fracture propagation mechanisms and inter-borehole superposition effects during liquid CO2 phase transition fracturing in coal seams - Yanbin Pei; Hongmin Yang; Wenlong Fu; Haiqing Zhang; Weifeng Shi; Shenqi Xiong; Shuchang Wan (Fuel, 2026)

High-efficient and reusable frictional-dissipating metamaterial based on compression-torsion coupling mechanism - Wen Jiang; Minghui Fu; Yanbin Wang; Hao Wu; Lingling Hu (Engineering Structures, 2026)

Biocontrol efficacy and antagonistic mechanisms of Bacillus velezensis L271 against Garlic Fusarium Rot caused by Fusarium solani - Shidong He; Dongliang Fang; Jinqi Wang; Liangshuai Fu; Junjie Liu; Yanbin Sun; Jinbiao Ma; Miao Zhou; Taotao Wang; Zheng Gao; Shuxin Zhang; Xiang Li (Postharvest Biology and Technology, 2026)

Graphene oxide/sodium alginate/silk fibroin extracellular matrix-like sponge for acellular and growth factor-free bone regeneration - Shuai Yang; Fengkun Wang; Haiyue Zhao; Yiran Zhang; Wei He; Peng Wang; Chunxu Fu; Wei Chen; Yanbin Zhu; Yingze Zhang (Carbohydrate Polymers, 2026)

Calculation method and application of discontinuous longitudinal deformation of shield tunnels considering variable stiffness of the ring joints - Yanbin Fu; Ning Liang; Yuehua Guo; Xiangsheng Chen; Ze Wu; Gendi Yelv; Xiaoping Li (Tunnelling and Underground Space Technology, 2025)

In situ multifunctional gel for hormone-immune therapy of ovarian cancer and prevention of postoperative adhesion - Yankun Zhang; Yanbin Shi; Hengchang Zang; Xiaogang Zhao; Xianglei Fu; Shengnan Qiu; Yuan Zhang; Yingying Liu; Xiaoyu Wan; Zengmei Li; Yaqi Li; Jiamin Zhou; et al. (Chemical Engineering Journal, 2025)

Mechanical properties and analytical solutions of ring linings in prestressed hydraulic tunnel - Yanbin Fu; Shun Wang; Liping Huang; Andian Lu; Yanlong Zhang; Xiaolong Zhang; Guangliang Yao; Yue Gao (Tunnelling and Underground Space Technology, 2025)

Effects of tannic acid on physicochemical properties of gluten-free flour and the underlying mechanisms - Yanbin Guan; Yaqiong Wang; Xun Yang; Li Li; Fu Shi; Miao Li; Mingjie Chen; Yuesheng Wang; Guangxiao Yang; Junli Chang; Guangyuan He; Yin Li (Food Hydrocolloids, 2025)

A novel nested compression-torsion metamaterial with independently customized mechanical properties - Wen Jiang; Minghui Fu; Lingling Hu; Yanbin Wang; Hao Wu (Engineering Structures, 2025)

Deformation prediction model of large-span prestressed structure for health monitoring based on robust Gaussian process regression - Wenwei Fu; Yi Chen; Yaozhi Luo; Hua-Ping Wan; Zhi Ma; Yanbin Shen (Engineering Structures, 2024)

Is milk fat globule size correlated with milk fat content in Ruminants? - Menglu Zhang; Zhentao Liu; Fangyuan Kang; Kuixian Wu; Han Ni; Yingqian Han; Yanbin Yang; Tong Fu; Guoyu Yang; Tengyun Gao; Liqiang Han (Food Chemistry, 2024)

An Anti-Windup Method Based on an LADRC for Miniaturized Inertial Stabilized Platforms on Unmanned Vehicles in Marine Applications - Tianlei Fu; Lianwu Guan; Yanbin Gao; Chao Qin (Journal of Marine Science and Engineering, 2024)
This paper investigates an anticipatory activation anti-windup approach based on Linear Active Disturbance Rejection Control (LADRC) to address the influences of accelerated saturation on the actuators in a Miniaturized Inertial Stabilized Platform (MISP) with extreme external disturbance. The proposed method aims to eliminate the high-frequency vibrations on the Line of Sight (LOS) of electro-optical devices during actuator saturation. To achieve this, the Linear Extended State Observer (LESO) is modified by adding saturation feedback to the total disturbance observed state variable, which is operated as an anticipatory activation anti-windup compensator. The stability of the proposed controller is discussed, and the gains are optimized by the Linear Matrix Inequality (LMI) constraints though quadratic programming and an H-infinite performance indicator. Additionally, as the multiple activated scheme for anti-windup, the effectiveness of immediate activation in dealing with accelerated saturation is compared and analyzed. These comparisons and verification are implemented through simulations, where the external disturbance is introduced using recorded attitude data from USV sailing. Finally, experiments are conducted on an MISP for a visual tracking system, demonstrating that the anticipatory activation mothed effectively suppresses high-frequency vibrations on the LOS during instances of accelerated saturation.

Analytical solution to the mechanical response of grouting lifting in existing shield tunnels and engineering case verification - Yanbin Fu; Shun Wang; Ze Wu; Xuezhong Zhang; Junzhou Zhu; Beiling Wang; Yelei Huang (Tunnelling and Underground Space Technology, 2024)

Prediction of the slurry pressure and inversion of formation characteristics based on a machine learning algorithm during tunnelling in a fault fracture zone - Xiang Shen; Yifan Chen; Liqiang Cao; Xiangsheng Chen; Yanbin Fu; Chengyu Hong (Tunnelling and Underground Space Technology, 2024)

Physiological and molecular mechanisms of boron in alleviating cadmium toxicity in Capsicum annuum - Chuang Shen; Huiling Fu; Baifei Huang; Qiong Liao; Yingying Huang; Yanbin Wang; Yating Wang; Junliang Xin (Science of The Total Environment, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

A new configuration of Geiger-type cable domes with sliding ridge cables: Computational framework and structural feasibility investigation - Yu Xue; Yaozhi Luo; Yafeng Wang; Xian Xu; Hua-Ping Wan; Yanbin Shen; Wenwei Fu (Engineering Structures, 2023)

The additive interactions between high-molecular-weight glutenin subunits and tannic acid improve the wheat quality - Yanbin Guan; Yaqiong Wang; Chuang Pan; Li Li; Fu Shi; Yuesheng Wang; Mingjie Chen; Guangxiao Yang; Guangyuan He; Junli Chang; Yin Li (Food Research International, 2023)

Theoretical analysis on horizontal rectification of tunnel near deep foundation pit by grouting - Yanbin Fu; Beiling Wang; Hao Wu; Xiangsheng Chen; Xiaohui Sun; Yuewei Bian; Xiang Shen (Tunnelling and Underground Space Technology, 2023)

A simplified deformation forewarning method for longitudinal structural performance of existing shield tunnels based on Fast Fourier Transform - Yanbin Fu; Fudao Wang; Chengyu Hong; Junsheng Wen; Deqi Zeng (Tunnelling and Underground Space Technology, 2023)

Transcriptome Sequencing of the Pale Anemones (Exaiptasia diaphana) Revealed Functional Peptide Gene Resources of Sea Anemone - Jinxing Fu; Yanbin He; Chao Peng; Tianle Tang; Aihua Jin; Yanling Liao; Qiong Shi; Bingmiao Gao (Frontiers in Marine Science, 2022)
Sea anemone venom is a marine drug resource library with pharmacological and biotechnology value, and it contains complex and diverse functional peptide neurotoxins. However, the venom components of only a limited number of sea anemone species have been globally evaluated by transcriptomics and proteomics. In this study, 533 putative protein as well as peptide toxin sequences were found on a large scale from dissimilar developmental stages of sea anemone Exaiptasia diaphana , which can be divided into 75 known superfamilies according to the predicted functions. Among them, the proportion of protein is 72.98%, and its main families are metalloproteases, chymotrypsinogen like, collagen, pancreatic lipase-associated protein like, and G-protein coupled receptor, while the proportion of peptides is 27.02%, and main families are ShK domain, thrombin, Kunitz-type, defensin, as well as insulin-like peptide. Finally, typical anemone peptide neurotoxins were screened, and the 3D structure and pharmacological activity of these anemone peptide neurotoxins were predicted by homology modeling. We elucidate on a valuable high-throughput approach for obtaining sea anemone proteins and peptides. Our findings form the basis for targeted studies on the diversity as well as pharmacological effects of sea anemone peptide neurotoxins.

Minimally Invasive Surgery with Spotlight Work Channel System in the Treatment of Lumbar Disc Herniation: A Retrospective Study of 21 Cases - Haidong Xu; Fengyu Jia; Yanbin Liu; Qiang Fu (Cell Biochemistry and Biophysics, 2015)